Clinical Leadership Mediating Nurses’ Knowledge and Motivation in Patient Safety Goal Implementation - Endang Triyani Kusuma Widyawati; Duta Liana; Kemala Rita Wahidi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The implementation of Patient Safety Goals remains a major challenge in hospital management, particularly in ensuring consistent compliance among nurses. This study aims to analyze the influence of nurses’ knowledge and motivation on the implementation of Patient Safety Goals, with clinical leadership positioned as a mediating variable. A quantitative cross-sectional design was employed in a general hospital in Jakarta, Indonesia. Data were collected from 119 nurses across inpatient, outpatient, emergency, and operating units using structured questionnaires. The data were analyzed using Structural Equation Modeling (SEM) with AMOS, supported by the Three-Box Method to assess the level of variable achievement. The results indicate that nurses’ knowledge and motivation have a significant direct effect on clinical leadership. Clinical leadership also demonstrates a significant positive effect on the implementation of Patient Safety Goals. Furthermore, clinical leadership plays a significant mediating role in the relationship between both nurses’ knowledge and motivation and the implementation of Patient Safety Goals. The model explains 76.67% of the variance in Patient Safety Goal implementation, highlighting the strategic role of clinical leadership in translating individual competencies into safe clinical practices. These findings contribute to healthcare management literature by reinforcing the importance of clinical leadership as an organizational mechanism that strengthens patient safety performance. From a managerial perspective, the study emphasizes that improving patient safety outcomes requires not only enhancing nurses’ knowledge and motivation, but also systematically developing clinical leadership competencies. Hospital management is encouraged to invest in leadership development programs, supportive supervision, and non-punitive incident reporting systems to ensure sustainable implementation of Patient Safety Goals.